2022
DOI: 10.1227/ons.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection in the Intensive Care Setting After Posterior Spinal Fusion: A Case Series Highlighting the Microbial Profile, Risk Factors, and the Importance of Comorbid Disease Burden

Abstract: BACKGROUND:Most posterior spinal fusion (PSF) patients do not require admission to an intensive care unit (ICU), and those who do may represent an underinvestigated, high-risk subpopulation.OBJECTIVE:To identify the microbial profile of and risk factors for surgical site infection (SSI) in PSF patients admitted to the ICU postoperatively.METHODS:We examined 3965 consecutive PSF patients treated at our institution between 2000 and 2015 and collected demographic, clinical, and procedural data. Comorbid disease b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, these series do not adjust for other commonly accepted risk factors for negative outcomes: The ISS is a well validated predictor of trauma-related mortality, and spine patients selected for ICU admission are a high-risk population known to have an elevated incidence of adverse events. 19 - 21 Fagin et al 37 did collect data on ISS but did not adjust or control for this or other confounders with respect to mortality rate. Fehlings et al 38 adjusted for demographic, comorbid disease burden, and ISS but did not examine mortality rate alone, instead assessing a compositive of death, worsened neck disability index, and treatment-related complications using Cox proportional hazards analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these series do not adjust for other commonly accepted risk factors for negative outcomes: The ISS is a well validated predictor of trauma-related mortality, and spine patients selected for ICU admission are a high-risk population known to have an elevated incidence of adverse events. 19 - 21 Fagin et al 37 did collect data on ISS but did not adjust or control for this or other confounders with respect to mortality rate. Fehlings et al 38 adjusted for demographic, comorbid disease burden, and ISS but did not examine mortality rate alone, instead assessing a compositive of death, worsened neck disability index, and treatment-related complications using Cox proportional hazards analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Moreover, spine patients selected for intensive care unit (ICU) admission are known to represent a high-risk patient subgroup; therefore, a providers' clinical judgment to select a patient for ICU admission is likely to be clinically relevant. 20 , 21 In addition, neurological impairment may spur the decision to pursue surgery and which may affect a patient's long-term function and prognosis. Without controlling for these factors, any calculated survival benefit associated with surgery is highly confounded.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] The authors conducted a retrospective study at a single institution over a 15-year period and identified 3965 patients who underwent PSF. 8 They examined the differences in microbial profile of SSIs in PSF patients admitted to the ICU vs non-ICU after surgery. They found that 16.2% of patients were admitted to the ICU postoperatively.…”
mentioning
confidence: 99%